Addressing Electroconvulsive Therapy Knowledge Gaps and Stigmatized Views Among Nursing Students Through a Psychiatrist–APRN Didactic Partnership. (May 2022) - Kitay, Brandon M.; Walde, Tina; Robertson, Dilice; Cohen, Tammy; Duvivier, Robbert; Martin, Andrés
BACKGROUND: Knowledge gaps and stigmatized perceptions regarding electroconvulsive therapy (ECT) among patients and health providers contribute to the underutilization of an important therapeutic modality. The proactive education of future advanced practice registered nurses (APRNs) provides an opportunity to optimize the use of this evidence-based clinical practice.AIMS: As part of a general course in psychiatry during the first year of nursing school, we dedicated 1 hour to treatment-refractory depression, including ECT, and a second hour to a summary discussion of mood disorders. We evaluated the efficacy of this didactic offering, which was co-taught by a psychiatrist and a psychiatric APRN.METHOD: At baseline, consenting students ( n = 94) provided three words they associated with ECT and then completed three validated instruments: (a) Questionnaire on Attitudes and Knowledge of ECT, (b) Opening Minds Stigma Scale for Health Care Providers, and (c) Self-Stigma of Seeking Help. Among the 67 students who repeated the assessment at endpoint, 39 attended the ECT didactic (Intervention group, 58%) and 28 did not (Control, 42%).RESULTS: After completion of the 3-month course, students showed improvement across all measures ( p < .001). The only outcomes that improved differentially between the Intervention and Control groups were the Questionnaire on Attitudes and Knowledge of ECT Attitudes and Knowledge scales ( p = .01). Word choice valence associated with ECT shifted favorably by endpoint ( p < .001).CONCLUSIONS: An educational intervention co-led by a psychiatric-mental health APRN had a significant impact on nursing students' knowledge and perceptions of ECT. This approach can be readily implemented at other institutions. Future refinements will include the videotaped depiction of a simulated patient undergoing the consent, treatment, and recovery phases of ECT.